Low plasma adiponectin levels in obsessive-compulsive disorder - Atmaca, Murad; Ustundag, Bilal; Metin, Kerem; Topuz, Mehtap (Elsevier, 2009)
This study was designed to examine plasma adiponectin levels in patients with obsessive-compulsive disorder (OCD). The plasma adiponectin and glucose concentrations were determined in 23 patients (13 females, 10 males) and age and sex-matched 23 healthy controls (14 females and 9 males). In measuring adiponectin levels, ELISA method was used. The mean adiponectin levels were 11.1 +/- 2.2 ng/ml for the patient group and 17.6 +/- 2.9 ng/ml for control group (P=0.00078). By using ANCOVA, significant difference in the mean adiponectin values continued after controlling for BMI or sex (F=6.04, P<0.013 adjusted for BMI; F=5.67, P<0.021 adjusted for sex). Despite some limitations, the present study suggests that there may be an interaction between OCD and plasma adiponectin. In this interaction, one should keep into mind both pathophysiologic dimension and cardiovascular vulnerability. But it is clear that although the present findings are of considerable significance they should be supported by the studies with larger sample. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: OCD; Adiponectin; Glucose